Capturing Debriefing and Enhancing Reflection within Simulated Clinical Learning Environments - Wareing, Mark; England, Jacqueline A; Mathew, David; Ball, Carla; Willetts, Amanda; Kemp, Jane; Clifford, Kelly; Thompson, Andrea; Dove, Ian; Adams, Louise (International Journal of Practice-based Learning in Health and Social Care, 2020)
This article presents findings from an evaluation of a new A3-size learner notes sheet designed for use by healthcare students engaging in clinical simulation and clinical skills sessions. The notes sheet consists of an adapted form of the SBAR (situation, background, assessment, response) tool, whilst capturing post-simulation oral debriefing provided by a facilitator. Additionally, the Driscoll (2007)model is used to provide students with an opportunity to reflect on their engagement in clinical simulation. Two cohorts of students, who engaged in separate simulation sessions, completed the A3 sheet. The study featured 33 midwifery and 21 operating department practitioner (ODP) students undertaking a simulation. Documentary analysis was undertaken to identify the depth of reflective writing of both groups of students. Midwifery student participants reflected on their experiences of simulation at a slightly deeper level than their ODP counterparts. All students adhered to the structure of the notes sheet when receiving their briefing from the facilitator and when asked to write their reflective accounts. This study has sought to explore an under-researched area of clinical simulation: the extent to which healthcare students can utilise reflection when engaging with a clinical scenario within a simulated learning environment.